2020
DOI: 10.3389/fneur.2020.00488
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Vitamins and Amyotrophic Lateral Sclerosis: A Center-Based Survey in Mainland China

Abstract: To date, conflicting results about the role of vitamins in amyotrophic lateral sclerosis (ALS) have been reported along with a lack of systematic studies on all types of serum vitamins in patients with ALS. Moreover, extensive studies have been conducted on vitamins in other neurodegenerative diseases; however, whether serum vitamin alterations in ALS are similar to those in other neurodegenerative diseases remains unclear. Therefore, we performed a study involving a large Chinese cohort of patients with ALS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 82 publications
2
24
0
1
Order By: Relevance
“…Volonté et al reported that histaminergic modulation might be effective in ALS because histamine-related genes were dysregulated in the cortex and spinal cord in sporadic ALS patients [ 43 ]. Folic acid (enrichment score = 0.757 and p -value = 6.60 × 10 −3 ) with vitamin B12 was reported to delay disease onset and prolong lifespans in the ALS mouse model [ 44 ]. Adenosine phosphate (enrichment score = 0.734 and p -value = 9.83 × 10 −3 ) is involved in adenosine homeostasis that may reportedly play important roles in ALS progression [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Volonté et al reported that histaminergic modulation might be effective in ALS because histamine-related genes were dysregulated in the cortex and spinal cord in sporadic ALS patients [ 43 ]. Folic acid (enrichment score = 0.757 and p -value = 6.60 × 10 −3 ) with vitamin B12 was reported to delay disease onset and prolong lifespans in the ALS mouse model [ 44 ]. Adenosine phosphate (enrichment score = 0.734 and p -value = 9.83 × 10 −3 ) is involved in adenosine homeostasis that may reportedly play important roles in ALS progression [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, extract of Korean red ginseng also prevented the activation of microglial cells and proinflammatory mediators and increased the activation of p38, NF-κb, JNK, and ERK MAPKs signaling pathways in striatum of a Huntington’s disease-like mice model induced by 3-nitropropionic acid [ 145 ]. In animal models of Alzheimer’s disease, studies revealed that vitamin C could reduce OS markers and Aβ formation, and restore behavioral deficits and memory impairment [ 146 ].…”
Section: Nutraceuticals In Nds: Multi-targeted Avenuementioning
confidence: 99%
“…Whether vitamin C deficiency might contribute to the development of ALS remains speculative and controversial. One cross-sectional study from China found lower serum vitamin C levels in PALS compared to healthy controls (8). Another found higher CSF vitamin C levels compared to healthy controls (9).…”
Section: Overviewmentioning
confidence: 99%